(untitled) (Scientific journal of the Fergana State University, 2025)
The article contains international legal documents on combating corruption, the UN Convention against Corruption, its norms on asset recovery, the Council of Europe Convention on Criminal Liability for Corruption dated 01/27/1999, one of the regional documents on the return of state assets, the Chisinau Convention on Legal Protection, Promotion and Regulation of Legal Relations, as well as the initiative A recommendation document on asset recovery in relations between participating States and the FATF Group’s recamendation, concerning the development of financial measures to combat illegal money laundering.